2014
DOI: 10.1103/physrevlett.112.146103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Limiting Thickness of Thin Oxide Films on Aluminum

Abstract: A first-principles account of the observed limiting thickness of oxide films formed on aluminum during oxidizing conditions is presented. The results uncover enhanced bonding of oxygen to thin alumina films in contact with metallic aluminum that stems from charge transfer between a reconstructed oxide-metal interface and the adsorbed molecules. The first-principles results are compared with the traditional CabreraMott (CM) model, which is a classical continuum model. Within the CM model, charged surface oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 36 publications
(42 reference statements)
4
71
1
Order By: Relevance
“…Costa et al [6] modelled an hydroxylated γ-(111) Al 2 O 3 film on Al(111). Baran et al [30] studied γ-Al 2 O 3 films on Al and found that the electronic properties of the film depend on the oxide thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al [6] modelled an hydroxylated γ-(111) Al 2 O 3 film on Al(111). Baran et al [30] studied γ-Al 2 O 3 films on Al and found that the electronic properties of the film depend on the oxide thickness.…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing iron thickness one further interesting phenomenon could be observed at low temperatures, brought about by an increasing importance of the interface between metal and oxide. As has been discovered long before [7][8], the magnetic switching properties of the ferromagnetic Fe metal are strongly changed by the action of the adjacent oxide which imposes a new type (601) of anisotropy onto the Fe metal, the so-called exchangebiasing (EB) or unidirectional anisotropy [1][2][3][7][8][9][10]. In this paper we show results on exchange coupling effects in naturally oxidised ultra thin Fe film (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Normally this process is depth limited such that an oxide covering layer with a well-defined thickness is formed by which the underlying metal is prevented from further oxidation. In this way one can obtain a self-stabilized metal/oxide bilayer structure [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Normally this process is depth limited such that an oxide covering layer with a welldefined thickness is formed by which the underlying metal is prevented from further oxidation. In this way one can obtain a self-stabilized bilayer structure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%